Hairspray [videorecording (DVD)] - Waters, John, 1946-; Bono, Sonny; Brown, Ruth, 1928-2006; Divine, 1945-1988; Harry, Debbie; Lake, Ricki; Stiller, Jerry; Fitzpatrick, Colleen, 1969-; St. Gerard, Michael, 1961-; Powers, Leslie Ann; Prince, Clayton; Stole, Mink; et al. (New Line Home Entertainment, 2005)
Tracy Turnblad, a spirited teenager, challenges segregation in 1962 Baltimore by landing a spot on The Corny Collins Show, impressing with her dance moves and winning over the host. As she rises to fame, Tracy's journey intersects with themes of racial integration and body positivity, while her newfound confidence inspires those around her to defy societal norms and embrace change. Alongside her romance with fellow dancer Link Larkin, Tracy's story unfolds against the backdrop of racial tensions and prejudice, culminating in a battle against discrimination and injustice.